Optimasi Biaya Distribusi Beras Sejahtera Menggunakan Metode Zero Suffix dan Metode ASM - Wida Karnila; Hendra Syarifudin; Meira Parma Dewi (Journal of Mathematics UNP, 2019)
Abstract – The research was distributed by the high cost of the prosperous rice distribution on perum bulog Bukittinggi Rp 219.986.865,-. Distribution is done from five warehouses to every subdistrict on the region it works. Perum bulog Bukittinggi striving for minimising the cost of every prosperous rice distribution warehouse to the districts. For minimising the cost of the prosperous rice distribution on perum bulog Bukittinggi used method zero suffix and the ASM method is a method of optimization of transportation problems and directly testing the keoptimuman transportation problem from the table without having to specify the initial solution first. The results of the calculation of the cost of distribution is performed by perum bulog Bukittinggi is Rp 219,986,865,-.Zero suffix using the method and the method of the ASM is Rp. 219,736,775.0-, so both of these methods can optimize the distribution cost issues bulog perum on without having to specify the initial solution.Keywords – zero suffix method, method of the ASM